A review on exergy analysis of vapor compression refrigeration system - Ahamed, Jamal Uddin; Saidur, Rahman; Masjuki, Haji Hassan (Elsevier, 2011)
This paper reviews on the possibilities of researches in the field of exergy analysis in various usable sectors where vapor compression refrigeration systems are used. Here, it is found that exergy depends on evaporating temperature, condensing temperature, sub-cooling and compressor pressure. It also depends on environmental temperature. Nowadays, hydrocarbons are considered as refrigerant having low ODP and GWP, and these are considerable in the aspect of exergy analysis. Refrigerants R 407a, R 600a, R 410a and R 134a are considered and analyzed with respect to exergy efficiency. Mixtures of hydrocarbons with R134a also show better performance with respect to other refrigerants. Among the components of the vapor compression system, much research showed that major part of exergy losses is occurred in the compressor. Nanofluid and nanolubricant cause to reduce the exergy losses in the compressor indirectly.